Model of the state policy for the development of enterprises in the hospitality industry - Valentyna Yakobchuk; Olga Zborovska; Svitlana Dombrovska; Iryna Dragan; Andrii Blyznyuk; George Abuselidze (E3S Web of Conferences, 2023)
The estimation of the basic tendencies of the development of enterprises in the hospitality industry in national and global scales wass carried out. Professional and qualified staff is the prerogative of any business, including hotel, because it is able to demonstrate the level of high-quality service. The main problems of an internal character concerning functioning and development of enterprises in the hospitality industry are allocated. Negative macroeconomic factors that affect the effectiveness of the state policy for the development in hospitality enterprises have been identified. Priority tasks have been formulated on the issues of improving the quality management in the hospitality enterprises, the solution of which will further develop specific measures to implement a quality-oriented model of the state policy for the development in the hospitality enterprises. This model should include elements of managing the process of providing services, new product development, deliveries and other elements that significantly affect the quality of service. It is proved that the structure of the model of the state policy for the development of enterprises in the hospitality industry is most reliably represented in the form of a set of subsystems: support functional and target subsystem.
Keywords: 330; State policy; Management; Enterprises; Hospitality industry